2011
DOI: 10.1002/aic.12293
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and simulation of flow properties of coal ash slag in coal gasification

Abstract: The viscosities of 45 coal ash slag samples at high temperature have been measured under different temperatures and shear rates. The computer thermodynamic software package FactSage has been used to predict liquidus temperatures, volume fractions of crystallized solid particles (/), and the compositions of remaining liquid phase for 45 coal ash slag samples. The flow properties of completely liquid and partly crystallized coal ash slag samples have been predicted by three viscosity models. The Urbain formalism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The kinetics of crystalline behavior is directly linked to degree of polymerization of melt (or viscosity) and is not well understood [95]. Despite limited theoretical understanding, heterogeneous slag viscosity can be predicted using thermodynamic models in conjunction with empirical viscosity models and/or combination of thermodynamic models and tools like HT-XRD [19,39,[96][97][98].…”
Section: Slag Mobilitymentioning
confidence: 99%
“…The kinetics of crystalline behavior is directly linked to degree of polymerization of melt (or viscosity) and is not well understood [95]. Despite limited theoretical understanding, heterogeneous slag viscosity can be predicted using thermodynamic models in conjunction with empirical viscosity models and/or combination of thermodynamic models and tools like HT-XRD [19,39,[96][97][98].…”
Section: Slag Mobilitymentioning
confidence: 99%
“…For entrained-flow gasifiers, it is important that the models describe the viscosity of fully liquid slag in multi-component slag systems and also predict the viscosity of partly crystallized liquid slag. For predicting the viscosity of homogeneous liquid slag, the models of Urbain, Fereday, and the silica percentage model are used, as well as modified versions of those models (such as Kalmanovitch-Urbain, Watt and Fereday, and S 2 ) [68,75,76]. The main challenge of all these models is their validity over a limited composition and temperature range, and their accuracy for different slag systems (e.g., Kalmanovitch model best predicts western coal slag above 1350 °C [77]).…”
Section: Slag Viscosity With Temperature and Slag Compositionsmentioning
confidence: 99%
“…The main challenge of all these models is their validity over a limited composition and temperature range, and their accuracy for different slag systems (e.g., Kalmanovitch model best predicts western coal slag above 1350 °C [77]). To predict the viscosity of the crystalline phase slags, Annen's or Einstein's models were used [68,76]. Most viscosity models are based on particular viscosity datasets and, therefore, can predict slag viscosity only for the specific compositions and temperatures.…”
Section: Slag Viscosity With Temperature and Slag Compositionsmentioning
confidence: 99%
“…Thus slag properties, especially the viscosity and flow behavior of the slag in the gasifier under high temperature as well as the char-slag transition process play important roles in the gasification process [4,5]. Several mechanical models have been proposed to predict slag formation and deposition characteristics in entrained-flow gasifiers [6,7] [8][9][10]. It has been identified that the viscosity of slag that can ensure a smooth tapping is lower than 25 Pa s. Further investigations are needed on the ash slag flow characteristics because they are widely recognized as the main potential area of concern in relation to the suitability of coals for use in entrained-flow coal gasifiers [11,12].…”
Section: Introductionmentioning
confidence: 99%